HUBUNGAN KESEHATAN DAN KESELAMATAN KERJA DENGAN KINERJA PERAWAT SELAMA PANDEMI COVID-19 - Eva Kartika Hasibuan; Masri Saragih; Adventy Riang Bevy Gulo (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Corona virus is a virus that can infect the respiratory system. In most cases, this virus only causes mild respiratory infections, such as the flu. However, this virus can also cause severe respiratory infections, such as lung infections. This condition is a challenge for nurses in providing nursing care to Covid 19 patients. Occupational health and safety is very important to implement, especially in companies that deal directly with patients so that their employees feel safe, comfortable, healthy and safe in doing their jobs, so that work productivity can be achieved effectively. optimal. This study aims to determine the relationship between occupational health and safety and the performance of nurses during the Covid-19 pandemic at Sari Mutiara Hospital. The research design used was an analytic survey design with a cross sectional approach. The population in this study were all nurses at Sari Mutiara General Hospital Lubuk Pakam. The sample in this study amounted to 60 people obtained by using total sampling. The data collection tool uses a questionnaire sheet. The statistical test used was the chi square test. The results showed that most of the nurses had occupational health and safety in the good category at 71.7% and the performance of nurses was in the good category at 65%. Statistical test results obtained pvalue = 0.002. The results of this study indicate that there is a relationship between occupational health and safety and the performance of nurses during the Covid-19 pandemic at Sari Mutiara Hospital. It is recommended for nurses to continue to comply with health protocols while carrying out their duties in providing services to patients, especially Covid 19 patients.